Criminal Liability of Passive Perpetrators in Money Laundering Crimes Involving the Families of State Officials - Agnes Cynthia; Kayowuan L, Kayus (Al-Risalah, 2025)
This research examines the criminal liability of passive perpetrators in money laundering cases, with a specific focus on the family of Syahrul Yasin Limpo (SYL), a former Indonesian Minister implicated in a high-profile corruption case. The primary purpose of this study is to explore whether individuals who indirectly benefit from illicit assets, without directly engaging in concealment, can be held criminally accountable under Indonesian anti-money laundering laws. Employing a normative legal research method, the study adopts both a statutory approach—analyzing Law No. 8 of 2010 on the Prevention and Eradication of Money Laundering—and a case approach through the judicial findings and evidence presented in SYL’s corruption trial. The results indicate strong grounds to suspect SYL’s family members as passive perpetrators, as they knowingly enjoyed the benefits of unlawful wealth through luxury lifestyles, property maintenance, and asset acquisition, without questioning the origin of the funds. These actions fulfill the elements required under Article 5, Paragraph (1) of the Money Laundering Law and suggest potential criminal liability. The originality of this research lies in its focus on passive actors—typically overlooked in legal practice—highlighting the legal and moral responsibility of beneficiaries in money laundering schemes. The findings imply a need for more comprehensive law enforcement strategies that include not only active perpetrators but also passive participants, in order to uphold the rule of law and combat impunity in corruption-related crimes.